Halogen bonding controlled 2D self-assembled polymorphism of regioisomeric thienophenanthrene derivatives by coadsorption. (31st March 2021) - Pang, Peng; Wang, Yi; Miao, Xinrui; Li, Bang; Deng, Wenli
Abstract : 5, 10-BTD-C14 molecules display self-assembled polymorphism in different bromo-hydrocarbons with different solution concentrations at the liquid/solid interface. Abstract : A thorough understanding of the halogen-bond-formation mechanism in surface-supported supramolecular assemblies is under explored compared with existing knowledge of hydrogen bonding. Here we report the self-assembly of regioisomeric bromine substituted thienophenanthrene derivatives (6, 9-DBTD-C14 and 5, 10-DBTD-C14) at the 1-bromo-hydrocarbon/highly oriented pyrolytic graphite (HOPG) interface. The chemical structures of these two kinds of molecules differ in the position of the bromine groups attached on the conjugated core. 6, 9-DBTD-C14 molecules assemble into a dumbbell-like linear adlayer in different 1-bromo-hydrocarbon solvents, such as bromotetradecane (C14-Br), bromopentadecane (C15-Br), and bromohexadecane (C16-Br) at different solution concentrations resulting from coadsorption by van der Waals interactions and possible halogen and hydrogen bonding. By contrast, the self-assembly of 5, 10-DBTD-C14 displays both solvent and concentration dependence. At the C14-Br/HOPG interface, only a mixed loose- and dense-packed backbone-like linear structure is obtained at different concentrations. At the C15-Br/HOPG interface, a dense-packed backbone-like linear structure at high concentrations and a matrix-like pattern at low concentrations are observed. At the C16-Br/HOPG interface, a loose-packed backbone-like linear structure at high concentrations and a bowknot-like linear adlayer at low concentrations are formed. The structural polymorphism derives from molecule–solvent van der Waals interactions between the alkyl chains and the halogen bonding between Br, S and –COO groups.